A REVIEW OF DIGITAL PAYMENT ADOPTION IN ASIA - Eko Susanto; Ikin Solikin; Budi Supriatono Purnomo, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2022)
Digital payments have changed people's financial behavior, particularly in Asian countries. The expansion of the internet network and the intensification of gadget functions have grown digital payment systems in mobile payments, internet banking, QR Codes, and electronic payments. Using a Systematic Literature Review, the study examined various Scopus articles from Asian countries to obtain an overview of the factors that influence the adoption of digital payments. We analyzed 597 digital, electronic, and mobile payment articles. TAM and UTAUT were found to be the most widely found theories to significantly affect user intent and even the continuity of digital payment use. While in the method, the structural equation model becomes the most widely used analytical method in various scientific publications related to this topic. This study has found internal and external factors from users in the adoption process of digital payments, including trust, perceived risk, satisfaction, security social influences, and facilitation conditions. Interestingly, some of these factors were insignificant in some studies due to differences in digital payment products that were the object of the study, respondents, and differences in research methods and approaches.